NURTURING FUTURE EXPERTS IN SCIENCE AND TECHNOLOGY FOR THE NATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 13 May 2017 The Society of Rising Individuals (SRI) in collaboration with Universiti Sains Malaysia (USM) and the Association of Science, Technology and Innovation (ASTI), has organised the Penang Science Fair for Young Children 2017.